WALI DALAM MISTIK ISLAM MENURUT REYNOLD A. NICHOLSON - Agus Himmawan Utomo (Jurnal Filsafat "WISDOM", 2012)
In Islamic tradition most people are known as ‘wali’ when they have miracle (karamah), such as healing people from blindness, transforming anything to another thing, etc.. Those karamah got muslims respect to the walis. Many cases show that they have privileges and permissions to behave or act which is different from common people. These privileges attract some persons to claim themselves as ‘wali’. The phenomena tends to position communities of one society in a destructive conflict because it is susceptible to manipulate the predicate of wali. According to Reynold A. Nicholson, the wali is everyone who is chosen by Allah. There is no boundaries of age, sex, race, or any other condition for the wali. Wali or aulia (plural) are chosen for their piety and ability to manage their desire, and because of their intimate relation to God, they had karamah. While Sufis are chosen from muslim community, aulia are chosen from the Sufis.